2021
DOI: 10.1111/gcb.15593
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensitivity of SOM decomposition is linked with a K‐selected microbial community

Abstract: Temperature sensitivity (Q 10 ) of soil organic matter (SOM) decomposition is a crucial parameter to predict the fate of soil carbon (C) under global warming. Nonetheless, the response pattern of Q 10 to continuous warming and the underlying mechanisms are still under debate, especially considering the complex interactions between Q 10 , SOM quality, and soil microorganisms. We examined the Q 10 of SOM decomposition across a mean annual temperature (MAT) gradient from −1.9 to 5.1°C in temperate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(122 citation statements)
references
References 114 publications
7
96
0
Order By: Relevance
“…In contrast, a large amount of newly generated organic matter was buried in the deep soil environment of the 10 years forest due to the influence of anthropogenic activities and the input of organic fertilizers and crop straw (Kramer and Gleixner, 2008). Along with this perennial plant residue lingering on the soil surface, which may increase anaerobic microsites and affect soil moisture and temperature and thus the decomposition of plant residues (Ramírez et al, 2020a), making a higher proportion of lignin and aromatic compounds in the surface soil, when the SOC is more difficult to be decomposed (Li et al, 2021). As restoration time and soil depth increased, humification in the soil would decrease, carbon from plants will increase, and organic matter in the soil will be more difficult to decompose.…”
Section: Influence Of Recovery Period On Soc Stability Of Larch Plantationsmentioning
confidence: 99%
“…In contrast, a large amount of newly generated organic matter was buried in the deep soil environment of the 10 years forest due to the influence of anthropogenic activities and the input of organic fertilizers and crop straw (Kramer and Gleixner, 2008). Along with this perennial plant residue lingering on the soil surface, which may increase anaerobic microsites and affect soil moisture and temperature and thus the decomposition of plant residues (Ramírez et al, 2020a), making a higher proportion of lignin and aromatic compounds in the surface soil, when the SOC is more difficult to be decomposed (Li et al, 2021). As restoration time and soil depth increased, humification in the soil would decrease, carbon from plants will increase, and organic matter in the soil will be more difficult to decompose.…”
Section: Influence Of Recovery Period On Soc Stability Of Larch Plantationsmentioning
confidence: 99%
“…Although the r /K strategy theory is oversimplified, it provides researchers with a fundamental ecological perspective for understanding mechanisms of assembly of microbial communities in response to environmental change (de Vries & Shade, 2013; Li et al, 2021). The increases in the relative abundances of Proteobacteria and Bacteroidetes with grassland degradation indicate that the bacterial community adopted r -selection strategies.…”
Section: Taxa Strategies In Response To Grassland Degradationmentioning
confidence: 99%
“…Environmental selection was potentially weak due to the rather mild changes in resources in the course of grassland degradation over the relatively small spatial and temporal scales. Nevertheless, environmental factors can indirectly influence community response strategies in the form of community assembly (Fierer et al, 2007;Li et al, 2021). The balance between r -and K -strategies mediated by community members of different phyla facilitates adaptation to resource loss under grassland degradation (Figure 6) .…”
Section: Taxa Strategies In Response To Grassland Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…But, due to higher labile SOC in the forest plantation which supported larger populations of soil microbes, Huang et al (2019) found that SOC mineralization was greater in the plantation forest than in the natural forest. The effects of soil properties on the Q 10 of SOC mineralization are also highly inconsistent (Wang et al 2019;Li et al 2021;Xu et al 2021). It was shown that the ratio of actinomycetes to bacteria (Liu et al 2017) and fungal phospholipid fatty acid (Qin et al 2019) were positively correlated with Q 10 , whereas the abundance of gram-negative bacteria decreased with the increasing Q 10 (Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%